2021
DOI: 10.1525/abt.2021.83.4.210
|View full text |Cite
|
Sign up to set email alerts
|

Planting a Native Pollinator Garden Impacts the Ecological Literacy of Undergraduate Students

Abstract: Ecological illiteracy exists, in part, because students may be technologically advanced but often lack intellectual curiosity about their natural environment. Botanical illiteracy, often referred to as “plant blindness,” results from several interacting factors, including a lack of interest in plants and insufficient exposure to plant science before students reach college. We were interested in understanding how a hands-on activity planting native plant species translates across undergraduate majors in improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The views in this article are similar to those of Hammarsten et al and Wells et al [ 51 , 52 ]. Among them, Wells et al advocated learning plant science knowledge, cultivating interest in plants and improving the ecoliteracy of participants through participation in horticultural activities.…”
Section: Discussionsupporting
confidence: 77%
“…The views in this article are similar to those of Hammarsten et al and Wells et al [ 51 , 52 ]. Among them, Wells et al advocated learning plant science knowledge, cultivating interest in plants and improving the ecoliteracy of participants through participation in horticultural activities.…”
Section: Discussionsupporting
confidence: 77%
“…The potential impacts extend to the level of funding allocated to plant conservation efforts (Balding & Williams, 2016), plant science research and enhanced participation in plant‐focused citizen science projects. To raise plant awareness and appreciation, an impressive diversity of approaches promoting botany in educational settings, as well as outside the classroom, has been proposed and developed (Crisci et al, 2020; Fančovičová & Prokop, 2011; Friesner et al, 2021; Jose et al, 2019; Levesley et al, 2012; McDonough Mackenzie et al, 2020; Moores et al, 2021; Pany et al, 2019; Thorogood, 2020; Woodland, 2007) with many demonstrating a measurable increase in botanical literacy among participants (Pinkerton et al, 2021; Ryplova & Pokorny, 2020; Stagg & Donkin, 2013; Wells et al, 2021). The growing number of initiatives run by plant scientists, such as international Fascination of Plants Day (https://plantday18may.org/), PlantLoveStories (https://www.plantlovestories.com) or More Than Weeds (https://morethanweeds.co.uk/), as well as relentless work of botanical gardens around the world, also continues to promote an awareness and appreciation of plants among the general public.…”
Section: Challenge: the End Of Botany?mentioning
confidence: 99%
“…Could this be one of first signs indicating that PAD is starting to decrease? Certainly, addressing this question is not trivial without further research, as PAD has not been measured or indeed continuously monitored at the national/societal scale, with most studies so far focused on educational settings, including groups of primary, secondary school or undergraduate students (Çil, 2015; Lindemann‐Matthies, 2005; Wells et al, 2021). However, a wave of interest in a range of plant‐related activities, products and industries has been clearly building over the last decade, likely with an additional impetus from the COVID‐19 pandemic.…”
Section: Google Search Volume Analysis Confirms: Plants Are Trendingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous studies of student knowledge of pollinators have found that students struggle with mechanisms of pollination as well as conservation practices (Golick et al 2018). Complex systems such as pollination may be oversimplified in primary education, and exposure through hands-on activities (such as citizen science projects) can improve ecological literacy in non-STEM majors (Wells et al 2021).…”
Section: Introductionmentioning
confidence: 99%